2015
DOI: 10.1177/0887403415619987
|View full text |Cite
|
Sign up to set email alerts
|

Federal Sentencing Guidelines and United States v. Booker: Social Context and Sentencing Disparity

Abstract: The United States v. Booker decision rendered Federal Sentencing Guidelines advisory rather than mandatory. In the context of this decision, this study examines both the direct influence of aggregate-level political, community, and administrative variables on sentencing outcomes, and the way that such characteristics might contextualize individual-level predictors. Using multi-level regression techniques, this study examines the role of aggregate-level variables on sentence length decisions across four distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
(137 reference statements)
0
4
0
Order By: Relevance
“… 2. We collect our district-level measures at the county level, and then aggregate them up into districts, because counties naturally fit within the federal districts (e.g., no county spills across multiple districts). While this technique will produce some level of measurement error, this is the most appropriate way to match Census data to federal districts, and previous studies of sentencing and social context have used this technique (see Feldmeyer & Ulmer, 2011; Kim, Cano, Kim, & Spohn, 2016; Nowacki, 2018). …”
mentioning
confidence: 99%
“… 2. We collect our district-level measures at the county level, and then aggregate them up into districts, because counties naturally fit within the federal districts (e.g., no county spills across multiple districts). While this technique will produce some level of measurement error, this is the most appropriate way to match Census data to federal districts, and previous studies of sentencing and social context have used this technique (see Feldmeyer & Ulmer, 2011; Kim, Cano, Kim, & Spohn, 2016; Nowacki, 2018). …”
mentioning
confidence: 99%
“…The minority-group threat hypothesis has been examined across a number of criminal justice outcomes. This body of research finds that large and growing non-white population size is associated with arrest decisions (Eitle and Monahan, 2009), police force strength (Carroll and Jackson, 1982; Jackson and Carroll, 1981; Jacobs, 1979), citizen complaints (Holmes, 2000; Smith BW and Holmes, 2003, 2014), sentencing outcomes (Nowacki, 2018; Wang and Mears, 2010), and police use of deadly force (Jacobs and O’Brien, 1998; Liska and Yu, 1992; Nowacki, 2015; Smith BW, 2004; Sorensen et al, 1993; Willits and Nowacki, 2014). Fewer studies have examined the link between racial composition and traffic enforcement (see Novak and Chamlin, 2012 for an exception).…”
Section: Minority-group Threatmentioning
confidence: 99%
“…Much of the literature on contextual variation in court processing has focused on inter‐district variation in sentencing practices (e.g., Johnson & DiPietro, 2012; Nowacki, 2018). This line of research has typically found wide variation in sentencing, which is impacted by urbanization, caseload, political pressure, and macro socio‐economic factors (Baumer & Martin, 2013; Johnson & DiPietro, 2012).…”
Section: Introductionmentioning
confidence: 99%